2022
DOI: 10.3390/ijms23158240
|View full text |Cite
|
Sign up to set email alerts
|

Microglia Remodelling and Neuroinflammation Parallel Neuronal Hyperactivation Following Acute Organophosphate Poisoning

Abstract: Organophosphate (OP) compounds include highly toxic chemicals widely used both as pesticides and as warfare nerve agents. Existing countermeasures are lifesaving, but do not alleviate all long-term neurological sequelae, making OP poisoning a public health concern worldwide and the search for fully efficient antidotes an urgent need. OPs cause irreversible acetylcholinesterase (AChE) inhibition, inducing the so-called cholinergic syndrome characterized by peripheral manifestations and seizures associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 47 publications
2
5
0
Order By: Relevance
“…We observed that DFP-exposed animals exhibited poor cognitive performance, shown by significant deficits in object recognition and spatial memory. Consistent with our study, other adult models of acute OP intoxication have also reported positive correlations between hippocampal neurodegeneration and cognitive impairment ( De Araujo Furtado et al, 2012 , Reddy et al, 2020a , b ; Somkhit et al, 2022 ). Inflammation signals in the hippocampus and amygdala, indicated by microglial activation, have also been proposed as a contributing factor to cognitive dysfunction as seen in an array of brain diseases, including epilepsy and Parkinson’s disease ( Guignet et al, 2020 ; Zhang et al, 2021 ; Somkhit et al, 2022 ; López-Meraz and Álvarez-Croda, 2023 ).…”
Section: Discussionsupporting
confidence: 92%
“…We observed that DFP-exposed animals exhibited poor cognitive performance, shown by significant deficits in object recognition and spatial memory. Consistent with our study, other adult models of acute OP intoxication have also reported positive correlations between hippocampal neurodegeneration and cognitive impairment ( De Araujo Furtado et al, 2012 , Reddy et al, 2020a , b ; Somkhit et al, 2022 ). Inflammation signals in the hippocampus and amygdala, indicated by microglial activation, have also been proposed as a contributing factor to cognitive dysfunction as seen in an array of brain diseases, including epilepsy and Parkinson’s disease ( Guignet et al, 2020 ; Zhang et al, 2021 ; Somkhit et al, 2022 ; López-Meraz and Álvarez-Croda, 2023 ).…”
Section: Discussionsupporting
confidence: 92%
“…In close agreement with data gained from both animal models and human patients [50], microglia displayed significant morphological differences in scn1Lab-KD larvae when compared to those in their not-injected siblings. In the mutant context, we observed a decreased number of "branched" microglia and an increased percentage of cells showing an "amoeboid" morphology, the latter resembling M1-type pro-inflammatory "activated" microglia observed following brain injuries or in various neuronal disease situations, including epilepsy [18], but also, as we previously showed, following intoxication by neurotoxic organophosphates [37,51]. Interestingly, although DS larvae showed an increased number of microglia with an "activated" phenotype, the proportion of "transitional" microglia was similar in the two genetic contexts, and a small, but significant, percentage (10%) of "branched" (resting) microglia was still observed in scn1Lab-KD individuals.…”
Section: Discussionsupporting
confidence: 75%
“…Cluster analysis, based on microglia morphology parameters, was performed as described in [37]. Briefly, five morphological parameters were quantified for each microglial cell: sphericity (S), number of processes (NP), total process length (TL), surface area (A), and volume (V).…”
Section: Morphological Clustering Of Microglial Cellsmentioning
confidence: 99%
See 2 more Smart Citations